THE RELATIONSHIP BETWEEN PERSONALITY TRAITS AND SELFREGULATED LEARNING WITH ACADEMIC PERFORMANCE OF STUDENTS IN ISLAMIC AZAD UNIVERSITY OF WEST MAZANDARAN PROVINCE (Singaporean Journal of Business Economics and Management, 2014)
The objective of the present study is to examine the relationship between personality traits and self-regulated learning with academic performance of students in Islamic Azad University of west Mazandaran province (Iran). Statistical population of the study includes all undergraduate students in Islamic Azad University of west Mazandaran province that are 16,686 students. The sample size was 375 students which was determined with the reference to the table of Krejcie and Morgan. Sampling was conducted by stratified random. Tools used to collect data included questionnaire of self-regulated learning by Zimmerman and Pons (2000), questionnaire of personality traits and scale of academic performance. Descriptive and inferential statistics were used to analyze the data. In inferential statistic, multiple regression analysis (stepwise model) and the Pearson correlation were used to assess hypotheses. The research findings showed that: There is positive significant relationship between personality traits, self-regulated learning with academic performance of students in Islamic Azad University of Mazandaran Province. There is positive significant relationship between personality traits and academic performance of students. There is positive significant relationship between self-regulated learning and academic performance of students.